2018
DOI: 10.5937/industrija46-14956
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic and specific banking determinants of nonperforming loans in Bosnia and Herzegovina

Abstract: The aim of the research is to identify the macroeconomic and specific banking factors affecting the rate of nonperforming loans in the banking sector of Bosnia and Herzegovina (BiH). The authors assume that the three macroeconomic and five specific banking factors influence the quality of the loan portfolio. Aggregate data were used, which are taken from the Central Bank of BiH, Agency for Statistics of BiH and Labour and Employment Agency of BiH, and analyzed by descriptive statistics, correlation and regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
2
0
1
Order By: Relevance
“…From the banking side, it indicates that there is a possibility of mismanagement of credit distribution by the bank. The results of this research are in a row with the results of the previous studies conducted by Ouhibi and Hammami (2015) and Agić and Jeremić (2018), which stated that GDP growth has a positive relationship and insignificant effect on NPL.…”
Section: The Impact Of Gdp On Nplsupporting
confidence: 81%
See 1 more Smart Citation
“…From the banking side, it indicates that there is a possibility of mismanagement of credit distribution by the bank. The results of this research are in a row with the results of the previous studies conducted by Ouhibi and Hammami (2015) and Agić and Jeremić (2018), which stated that GDP growth has a positive relationship and insignificant effect on NPL.…”
Section: The Impact Of Gdp On Nplsupporting
confidence: 81%
“…The Unemployment rate is the percentage of people's total amount in the labor force that is unemployed (Krugman & Wells, 2021). Mileris (2014), Szarowska (2018), Mazreku et al (2018), and Agić and Jeremić (2018) claimed that the unemployment rate has a significant affects the NPL. When the unemployment rate increased, it will affect the rise of the NPL ratio.…”
Section: Unemployment Ratementioning
confidence: 99%
“…Pašić and Omerbegović-Arapović (2016) investigated macroeconomic factors of non-performing loans in households sector of Federation of Bosnia and Herzegovina and found negative association between GDP growth and NPLs while inflation and unemployment were not significant predictors. Somewhat different results were obtained by Agić and Jeremić (2018) who analyzed macroeconomic and bank-specific factors of NPLs in Bosnia and Herzegovina during the 2006-2016 period. The authors found that rising NPLs are correlated with high unemployment rate, growth of consumer prices, return on assets and credit growth rates, while the effects of the GDP growth, capital adequacy ratio, return on equity and active interest rates are not statistically significant.…”
Section: Literature Reviewmentioning
confidence: 84%
“…Berkaitan dengan variabel kontrol tingkat pengangguran, ketika tingkat pengangguran meningkat, maka akan mempengaruhi kenaikan tingkat default karena meningkatnya angka pengangguran akan memicu turunnya kemampuan masyarakat dalam menyediakan arus kas dan menurunkan kemampuan debitur dalam membayar utang kepada bank (Krugman, 2021). Hasil ini tidak sejalan dengan Mileris (2014), Szarowska (2018), Mazreku et al (2018), dan Agić & Jeremić (2018) menyatakan bahwa tingkat pengangguran berpengaruh signifikan terhadap tingkat default karena ketika tingkat pengangguran meningkat, maka akan mempengaruhi kenaikan tingkat default.…”
Section: Hasil Dan Pembahasanunclassified